AS PRÁTICAS INTERCULTURAIS NA ESCOLA INDÍGENA TERENA DE LALIMA: os desafios de uma educação escolar diferenciada - Eduardo Dos Santos Rodrigues (2023)
ABSTRACT In Brazil, for a long time, educational practices aimed at indigenous people had the objective of civilizing, assimilating and integrating them into national society. With the Federal Consti-tution of 1988 (CF88) this conception changed, making possible the contribution of indige-nous populations to indigenous school education, transforming it into a specific, differentiated and intercultural education, in its own way. It is in this context that the present work is insert-ed, with the general objective of analyzing the challenges of the intercultural practices of in-digenous teachers in two indigenous schools located in Aldeia Lalima (Terra Indígena de Lalima), in Miranda, in the State of Mato Grosso do Sul. The methodology used for this work was a bibliographic review of authors who study the subject, also using Anthropology's own methods, including participant observation and autoethnography, that is, carrying out field work in dialogue with the experience of the author of this work, who is an indigenous teacher in the aforementioned village. The research points to the existence of some changes in teach-ing practices in indigenous school education in Lalima post-CF88, however, with difficulties, challenges, walking, therefore, at a slow pace. Among the challenges observed in the field, we note the ambiguity of the term intercultural in its relationship with internal coloniality. Thus, a way to advance in the process of conquering a more complex intercultural indigenous school education would be to assume a critical decolonial stance, as a guiding perspective for over-coming inequality, internal colonialism, towards the construction of an indigenous school edu-cation closer to what that we found in the legal molds. KEYWORDS: Terena; Intercultural practices; Indigenous School Education; Autonomy, Decoloniality.